L'ère électrique - The Electric Age - Oberhuber, Andrea (Cultural Transfers, 2011)
The scientific discovery and mastery of electricity created as many important changes in modern society as did the invention of alphabetical writing in antiquity and movable type in the fifteenth century. It is more than a natural phenomenon that science has harnessed for human use; it is a central feature of the modern episteme. It has inspired writers and artists, propelled industry and innovation, and reshaped human social behaviour. Looking at a variety of topics including film, politics, and contemporary art, this volume explores the impact of electricity on knowledge, social practices, media, community life, and subjective experience.